In vitro effects of antidepressants and mood-stabilizing drugs on cell energy metabolism - Cikánková, Tereza; Fišar, Zdeněk; Hroudová, Jana (Naunyn-Schmiedeberg's archives of pharmacology, 2020)
The evaluation of drug-induced mitochondrial impairment may be important in drug development as well as in the comprehension of molecular mechanisms of the therapeutic and adverse effects of drugs. The primary aim of this study was to investigate the effects of four drugs for treatment of depression (bupropion, fluoxetine, amitriptyline, and imipramine) and five drugs for bipolar disorder treatment (lithium, valproate, valpromide, lamotrigine, and carbamazepine) on cell energy metabolism. The in vitro effects of the selected psychopharmaca were measured in isolated pig brain mitochondria; the activities of citrate synthase (CS) and electron transport chain (ETC) complexes (I, II + III, and IV) and mitochondrial respiration rates linked to complex I and complex II were measured. Complex I was significantly inhibited by lithium, carbamazepine, fluoxetine, amitriptyline, and imipramine. The activity of complex IV was decreased after exposure to carbamazepine. The activities of complex II + III and CS were not affected by any tested drug. Complex I-linked respiration was significantly inhibited by bupropion, fluoxetine, amitriptyline, imipramine, valpromide, carbamazepine, and lamotrigine. Significant inhibition of complex II-linked respiration was observed after mitochondria were exposed to amitriptyline, fluoxetine, and carbamazepine. Our outcomes confirm the need to investigate the effects of drugs on both the total respiration rate and the activities of individual enzymes of the ETC to reveal the risk of adverse effects as well as to understand the molecular mechanisms leading to drug-induced changes in the respiratory rate. Our approach can be further replicated to study the mechanisms of action of newly developed drugs.
Keywords: Subcellular Fractions; Electron Transport Chain Complex Proteins; Animals; Antimanic Agents; Mitochondrial respiration; Antidepressive Agents; Mitochondria; antimanika; buněčné dýchání; Sus scrofa; subcelulární frakce; Oxidative Phosphorylation; mozek; Citrate synthase; Antidepressant; mitochondrie; elektronový transportní řetězec; oxidativní fosforylace; Brain; Cell Respiration; Mood-stabilizing drugs; zvířata; Electron transport chain complexes; antidepresiva